MAHABBAH AND MODERATE EDUCATION: A THEMATIC HADITH STUDY IN COUNTERING RADICALISM - M. Aris Akin; Muhammad Sabir Maidin; Arifuddin Ahmad (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The spread of contemporary religious radicalism, which has fueled the growth of exclusive attitudes, intolerant behavior, and actual acts of violence within Islamic educational institutions, forms the background for this scientific study. These operational issues demand a thorough reconstruction of the governance of a spiritual-values-based pedagogical paradigm to fortify the mentality of the younger generation. The main focus of this research is a comprehensive examination of the concept of mahabbah (community) in the collection of hadith texts and an analysis of its substantial relevance as a philosophical foundation for moderate Islamic education to counter radicalism. The research steps were carried out systematically using qualitative library research methods through a thematic hadith study approach. The secondary data collection procedure in the field involved authenticity verification (takhrij), chain of narrators' continuity critique, comparative textual analysis, and normative-contextual interpretation. The research findings, from the aspect of i'tibar criticism, prove the authenticity of the hadith narrated by Bukhari and Muslim as sahih, strengthened by the existence of mutabi'at (authentic) and shawahid (authentic narrators). Conceptually, the values ​​of compassion embody the commandments of universal love, ijtimaiyyah brotherhood, and the implementation of the preventive method of sadd al-dzari'ah to eradicate the seeds of sectarian prejudice. The main conclusion confirms that the internalization of a compassion-based curriculum has proven successful in transforming learning spaces into inclusive, humanistic, and tolerant ecosystems. This affective guidance pattern is highly recommended for curriculum practitioners as an essential curative strategy for producing a resilient wasathiyyah generation that will face ongoing global challenges.   ABSTRAK Merebaknya paham radikalisme keagamaan kontemporer yang memicu tumbuhnya sikap eksklusif, perilaku intoleran, dan aksi kekerasan nyata di dalam satuan pendidikan islam melatarbelakangi kajian ilmiah ini. Masalah operasional tersebut menuntut adanya rekonstruksi mendalam pada tata kelola paradigma pedagogis berbasis nilai spiritual guna membentengi mentalitas generasi muda. Fokus utama penelitian ini adalah mengkaji secara komprehensif konsep mahabbah dalam kumpulan teks hadis serta menganalisis relevansi substansialnya sebagai fondasi filosofis pendidikan islam moderat untuk menangkal gerakan radikalisme. Langkah-langkah penelitian dijalankan secara sistematis menggunakan metode studi kepustakaan (library research) kualitatif melalui pendekatan kajian hadis tematik. Prosedur pengerjaan data sekunder lapangan dieksekusi lewat tahapan verifikasi otentisitas (takhrij), kritik kontinuitas sanad, analisis tekstual komparatif, hingga penafsiran normatif-kontekstual. Temuan penelitian dari aspek kritik i'tibar membuktikan otentisitas hadis riwayat Bukhari dan Muslim berada pada status sahih yang diperkuat oleh eksistensi mutabi'at serta shawahid. Secara konseptual, nilai-nilai mahabbah mengejawantahkan perintah kasih sayang universal, ukhuwah ijtimaiyyah, serta implementasi metode preventif sadd al-dzari'ah untuk meruntuhkan bibit prasangka sektarian. Simpulan utama menegaskan bahwa internalisasi kurikulum berbasis cinta kasih terbukti sukses mentransformasikan ruang belajar menjadi ekosistem yang inklusif, humanis, dan toleran. Pola bimbingan afektif ini sangat direkomendasikan bagi praktisi kurikulum sebagai strategi kuratif esensial untuk melahirkan generasi wasathiyyah yang tangguh menghadapi tantangan global berkelanjutan.